Indian Ocean warming modulates global atmospheric circulation trends - Dhame, S; Taschetto, AS; Santoso, A; Meissner, KJ (Climate Dynamics, 2020)
The Indian Ocean has warmed rapidly and notably at a faster rate than the other tropical ocean basins in the latter half of the twentieth century. We conduct sensitivity experiments using an atmospheric general circulation model to determine the impact of Indian Ocean surface warming on large-scale global atmospheric circulation trends and rainfall distribution, in terms of its pattern and magnitude. Indian Ocean warming drives changes in the local Indian Ocean Walker cell that leads to anomalous easterlies over the Pacific Ocean and strengthens the Pacific Walker Circulation. The anomalous Indian Ocean Walker cell results in anomalous subsidence over Central Africa and the tropical Atlantic, where it is associated with a precipitation decrease over the equator. During austral summer, Indian Ocean warming is associated with the intensification of the northern hemisphere Hadley cell and strengthening of the extratropical atmospheric circulation resembling a positive North Atlantic Oscillation. During austral winter, it is associated with weakening of the southern hemisphere Hadley cell and strengthening of a positive Southern Annular Mode pattern. More intensive warming in the western region of the Indian Ocean basin compared to the east has a significant impact on rainfall trends in the basin, easterly wind trend in the western Pacific and intensity of Hadley circulation changes. It is, however, the Indian Ocean warming across the entire basin that dominates the drying of the tropical Atlantic and the trends in extratropical modes of variability. This study suggests the Indian Ocean warming could have potentially influenced global atmospheric circulation trends observed in the recent decades.